Empowerment of PKK Members in Training for the Production of Red Dragon Fruit Peel Tisane in the Kauman Subdistrict of Malang City - Venny Kurnia Andika; Ani Riani Hasana; Sirilus Deodatus Sawu (Journal of Community Practice and Social Welfare, 2023)
Tisane is an infusion beverage composed of a mixture of various ingredients such as leaves, seeds, herbs, legumes, tree bark, fruits, or flowers that are dried, or parts of plants that provide aroma and flavor while also being beneficial for health. Tisanes can offer health benefits such as antioxidant, antimicrobial, antihemolytic, and cytotoxic activities. Red dragon fruit peel contains a significant amount of natural anthocyanin colorants, rich in polyphenolic compounds, betalain compounds, vitamins C, E, and A, alkaloids, terpenoids, flavonoids, thiamine, niacin, pyridoxine, cobalamin, phenolics, carotenes, and phytoalbumins, making it a potential source of natural antioxidants. Therefore, red dragon fruit peel can be used to make tisanes due to its proven health benefits. Empowering members of the PKK (Family Welfare Movement) in the Kauman Subdistrict of Malang City in tisane production aims to increase the knowledge and skills of PKK members regarding the benefits and methods of tisane production using red dragon fruit peel waste. The community service activity was conducted in three phases. The first phase involved an explanation of the health benefits of tisanes. The second phase covered the method of making tisanes using red dragon fruit peel, and the third phase included practical tisane production and evaluation. Evaluation results showed an improvement in participants' understanding, with an average pretest score of 61.74 and an average post-test score of 90.87, with an average participant skill score of 28.61 (categorized as skilled). This indicates that the information provided about tisane production was well-understood by the participants, indicating the success of the community service activity. Throughout the activity, participants interacted well and responded by asking questions about the community service activity.